Предмет: Алгебра, автор: PANDA220

Упростите выражение:

Приложения:

Ответы

Автор ответа: NNNLLL54
0
left ( frac{3}{x^{1/4}+y^{1/4}} + frac{3}{x^{1/4}-y^{1/4}} right )cdot  frac{y^{-1/2}-x^{-1/2}}{4x^{-1/4}y^{-1/2}} = frac{3cdot 2x^{1/4}}{x^{1/2}-y^{1/2}} cdot  frac{x^{1/4}y^{1/4}(x^{1/2}-y^{1/2})}{4cdot x^{1/2}y^{1/2}} =\\= frac{3cdot x^{1/2}y^{1/4}}{2x^{1/2}y^{1/2}} = frac{3}{2y^{1/4}} =1,5cdot y^{-frac{1}{4}}
Похожие вопросы
Предмет: Химия, автор: nurlbhicgh
Предмет: Математика, автор: асел1